INNOVACIYALIQ TEXNOLOGIYALAR JÁRDEMINDE ANA TILI SABAQLARINDA ALMASIQ SÓZ SHAQABIN OQITIW METODIKASI - Sultanova, A.; Yeshniyazova, G. (SCIENCE and SOCIETY, 2022)
This article talks about the importance of teaching pronouns using innovative technologies and presents some of these interactive methods.